Can motorways develop car industry ?. Issue 3 (2015) - Turi, Attila; Mocan, Marian; Ivascu, Larisa; Goncalves, Gilles
Abstract: The paper outlines the role and importance of motorways in supporting both the automotive industry and the global economy of emerging countries. Investing in motorways is one of the easiest ways to support and assure economic development on short- and long-term and a means to overcome the car market decrease, redesign supply chains and improve overall competitiveness. Economic data and indicators of the automotive industry from Germany, France and Romania are analysed and compared providing an overview on market dynamics and perspectives. Results show that drivers of economic and automotive industry development are mainly linked with infrastructure and its interrelated effects. Thus, the benefits generated by job creation, average salary increase and overall macroeconomic improvement will provide a source of wellbeing for the population of a country and generate economic growth.